Análisis de la disponibilidad hídrica de la cuenca del Río Catamayo, hasta la estación en Pte. Vicin, con fines de aprovechamiento y conservación - Cuenca Rosillo, Alex Darwin (2015)
This research was conducted in the River Basin Catamayo specifically to the hydrometric station in Vicin bridge site covering 37.31% of the total area of the province of Loja, with the main objective to contribute to a better use and conservation water resources of the basin, through the identification of areas of increased water production in the period 1990 - 2010, proposing: 1). Determine the availability of water in basins with hydrological records, through the construction of the discharge curves, from the levels recorded in the hydrometric stations. 2) Estimate water availability in basins without hydrological records, through empirical methods. 3). Identify areas of higher water intake from the basin to the station in Vicin bridge, using GIS support. The basic information required for the conduct of the research was: statistical meteorological data from the closest places to the area of study, statistical data hydrometric stations within the study site stations, updated map data and a digital terrain model (DTM ) for the use of GIS (Geographical Information System) allowing to perform a morphometric study of the area, and in subsequent make interpretations about the basins and to estimate rainfall and runoff produced in them, which allowed an appraisal of the areas of higher water supply watershed, for purposes of use and conservation. The results indicate good hydrological condition of the basin, throughout the whole year near 1757.41Km2 (42.3%) of the total area of the basin of the river Catamayo has a very high retention and humidity control, gaining an average annual runoff between 1000 and 1250 mm, representing a volume of water of 1134, 39 mm3, the flow generated by empirical methods maintain a 98% correlation, while the real flow there are 60%, methods relating variables as hydrologic soil groups, slopes, vegetation cover, which can be used to make approximations of hydrological conditions and likewise identify areas of increased water production of the basin.